2016
DOI: 10.1016/j.exger.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of the effects of age on the blood plasma metabolome in the common marmoset, Callithrix jacchus

Abstract: Primates tend to be long-lived for their size with humans being the longest lived of all primates. There are compelling reasons to understand the underlying age-related processes that shape human lifespan. But the very fact of our long lifespan that makes it so compelling, also makes it especially difficult to study. Thus, in studies of aging, researchers have turned to non-human primate models, including chimpanzees, baboons, and rhesus macaques. More recently, the common marmoset, Callithrix jacchus, has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 46 publications
0
28
1
Order By: Relevance
“…Investigations into the metabolism-aging interplay focusing on changes at the level of the metabolome have been increasingly reported in a variety of model organisms (Hoffman et al, 2016; Laye et al, 2015; Lewis et al, 2018; Ma et al., 2015; Pontoizeau et al, 2014). Studies have also been conducted in humans, including one report linking several lipid species to human longevity (Gonzalez-Covarrubias et al, 2013) and another noting associations among citric acid cycle intermediates and bile acids on the lifespan in humans (Cheng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations into the metabolism-aging interplay focusing on changes at the level of the metabolome have been increasingly reported in a variety of model organisms (Hoffman et al, 2016; Laye et al, 2015; Lewis et al, 2018; Ma et al., 2015; Pontoizeau et al, 2014). Studies have also been conducted in humans, including one report linking several lipid species to human longevity (Gonzalez-Covarrubias et al, 2013) and another noting associations among citric acid cycle intermediates and bile acids on the lifespan in humans (Cheng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also been conducted in humans, including one report linking several lipid species to human longevity (Gonzalez-Covarrubias et al, 2013) and another noting associations among citric acid cycle intermediates and bile acids on the lifespan in humans (Cheng et al, 2015). However, arriving at consensus changes that define the aging metabolome has proven somewhat elusive, given the inherent complexity of the metabolome, as well as other variables across studies (De Guzman et al, 2013; Hoffman et al, 2016; Kim et al, 2014; Ma et al., 2015). Furthermore, to what extent changes to the aging metabolome are amenable to interventions such as DR, and more important, the human relevance of these observations, is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, age-related changes in protein concentrations are seen in mosquitoes [84], honeybees [85], sea urchins [86], and macaque hearts [87], and age-related longitudinal changes in metabolites have been measured in the common marmoset [88]. In addition, metabolite concentrations are correlated with longevity across 26 mammalian species [89], leading to new insights into how metabolite concentrations change across species with highly variable lifespans.…”
Section: Proteomics and Metabolomics As Ageing Biomarkersmentioning
confidence: 99%
“…Work in Drosophila found significant down-regulation of fatty acid and sugar metabolism with age [69], and a study of metabolite pathway enrichment in dietary restricted flies showed a global decline in amino acid metabolism in response to dietary restriction [35]. Metabolomic profiles in aged mouse brains show significant changes in amino acid and nucleotide metabolism [82], and nucleotide metabolism is significantly altered with age longitudinally in the common marmoset [88]. In addition, energy metabolism and amino acid metabolism are significantly altered in Alzheimer’s patients compared with cognitively normal individuals [94].…”
Section: Metabolic Pathways Associated With Ageingmentioning
confidence: 99%